FORMATION OF MANAGERIAL, MARKETING AND LEGAL COMPETENCE IN HIGHER EDUCATION STUDENTS WHILE STUDYING THE PHARMACEUTICAL MARKET OF UKRAINE - Садогурська, Катерина; Грешко, Юлія; Басараба, Роксолана (SWorldJournal, 2025)
The article examines the educational and methodological foundations of forming managerial, marketing, and legal competencies in higher education applicants majoring in 226 “Pharmacy, Industrial Pharmacy” at the master’s level in the process of studying th